PENGARUH WAKTU PEMBERIAN PUPUK KANDANG SAPI TERHADAP P TERSEDIA DAN SERAPAN P SERTA HASIL TANAMAN BAWANG MERAH (Allium Ascalonicum L.) VARIETAS BIMA. - Arifin Salewan; Abd Rahim Thaha; Muh. Adnan Khaliq (Fakultas Pertanian, Universitas Tadulako, 2022)
The objective of this research was to investigate cow manure application at various intervals effects on the availability of P, P uptake, and yields of Bima shallot variety grown on Entisols Sidera. The study was conducted at Faculty of Agriculture of University Tadulako with soil and plant analysis performed at the Soil Science Laboratory. The research was carried out between October 2018 and January 2019, and a randomized block design with three repetitions was utilized. The treatments involved applying 27.37 g of fertilizer with different time of application, i.e at the same time as planting (W0), one week before planting (W1), two weeks before planting (W2), three weeks before planting (W3), and four weeks before planting (W4). The findings revealed that applying cow manure at a rate of 27.37 g at different times can increase P-Total, pH H2O, pH KCl, plant growth, and P uptake on Entisols Sidera.